ナンキョク ヒガシ クィーンモードランド ナイリク ヒョウショウ ニ オケル ユキ ノ セッピョウ ガク テキ ナラビ ニ カガク テキ トクセイ - 神山, 孝吉; カミヤマ, コウキチ; 上田, 豊; アゲタ, ユタカ; 奥平, 文雄; オクヒラ, フミオ; 藤井, 理行; フジイ, ヨシユキ; 渡辺, 興亜; ワタナベ, オキツグ; Kamiyama, Kokichi; Ageta, Yutaka; et al. (1987)
P(論文) 1985年に行った東クィーンモードランド氷床内陸部の調査により, その頂部Valkyrjedomenの最高地点(77°22′S, 39°37′E, 3807m)やその氷床表面形態が明らかになったほか, 雪の地球化学的特性がわかった。内陸に向かうにしたがい, 雪の電気伝導度は大きくなり, pHは低くなる傾向が認められたが, 特に標高3600m以上の内陸部でこの傾向が顕著であった。これは南極氷床内陸部では, 成層圏起源のエアロゾルやガスが, 雪の化学的特性を規定しているためと考えられる。 Glaciological observations on the high plateau in the East Queen Maud Land, Antarctica, were carried out along a route of the oversnow traverse, by the 25th and 26th Japanese Antarctic Research Expeditions in 1984 and 1985. The surface topography of the dome-like plateau (Valkyrjedomen, which is the second highest in Antarctica) and the positions of ice divides were determined clearly. The position and altitude of the highest place of the dome are 77°22′S, 39°37′E and 3807m a.s.l. Snow drift samples were collected along the route from Mizuho Station to Valkyrjedomen and were melted carefully in a snow vehicle. The value of electric conductivity of the melted snow samples at 0℃ was obtained before storing in the pre-cleaned bottles. In a home laboratory, pH measurements of the samples were carried out. It was revealed that the high electric conductivity and low pH values were found among the snow samples collected in the dome area, especially around the region higher than 3600m a.s.l. The region has the different glaciological characteristics from those in the katabatic wind region, that is, the lower degree of the surface inclinations, the lower net accumulation, the more smooth surface morphology, the lower ram hardness of surface snow layer and the higher lapse rate of snow temperature at 10m depth. Taking the comparatively higher concentration of artificial radio nuclides reported in the other Antarctic inland area into consideration too, the glacio-chemical environments in the Antarctic inland region are thought to be characterized by the transportation of the stratospheric aerosols or gases. departmental bulletin paper